Satisfacción del usuario en consulta externa de la Clínica Central de Montería en el cuarto trimestre del 2021 (2022)
Rodríguez et, al (2020) indicate that the analysis of health services allows identifying the origin and scope of failures that can cause dissatisfaction in users, prevalence of diseases, adverse events, the so-called walk of death, where they die patients due to lack of attention and complaints from users who, not being attended to, go to the control entities and judges to defend their rights, generating administrative trauma and high costs for compensation. Therefore, the analysis of the topic is carried out Determining the level of user satisfaction in the outpatient service of the Central Clinic of Montería. Using the descriptive study methodology, with a qualitative approach. Information was collected, for which the SERVQUAL model was applied, which evaluates user satisfaction and assesses five dimensions. Among the results obtained, there is evidence of 65% satisfaction, placing it at the medium level in relation to the service provided by the clinic's nurses; Similarly, 15% of the patients in the survey carried out show a high level of satisfaction in the attention of the administrative staff; the remaining 20% of the patients seen in the outpatient service show a low level of satisfaction. In the assessment for the development of daily activities according to quality, sense of belonging, love for their profession, empathy with the user or patient with 90% satisfaction.